Imaging and Analysis of Isomeric Unsaturated Lipids through Online Photochemical Derivatization of Carbon–Carbon Double Bonds. (26th February 2021) - Unsihuay, Daisy; Su, Pei; Hu, Hang; Qiu, Jiamin; Kuang, Shihuan; Li, Yingju; Sun, Xiaofei; Dey, Sudhansu K.; Laskin, Julia
Abstract: Unraveling the complexity of the lipidome requires the development of novel approaches for the structural characterization of lipid species with isomer‐level discrimination. Herein, we introduce an online photochemical approach for lipid isomer identification through selective derivatization of double bonds by reaction with singlet oxygen. Lipid hydroperoxide products are generated promptly after laser irradiation. Fragmentation of these species in a mass spectrometer produces diagnostic fragments revealing the C=C locations in the unreacted lipids. This approach uses an inexpensive light source and photosensitizer making it easy to incorporate into any lipidomics workflow. We demonstrate the utility of this approach for the shotgun profiling of C=C locations in different lipid classes present in tissue extracts using electrospray ionization (ESI) and ambient imaging of lipid species differing only by the location of C=C bonds using nanospray desorption electrospray ionization (nano‐DESI). Abstract : Rapid derivatization of lipids using a photoinitiated reaction with singlet oxygen provides insights into the C=C bond location in the precursor lipid through diagnostic CID fragments. This method is compatible with lipidomics workflows and can be adapted for the analysis of tissue extracts and for imaging of isomeric lipids in tissue sections.